Depression and suicidality among Egyptian renal transplant recipients - Naglaa El-Mahalawy (Middle East Current Psychiatry, 2020)
Abstract Background High rates of depression and suicidality risk have been reported after renal transplantation. The study aims to estimate the prevalence of depressive disorders and suicidality risk among Egyptian renal transplant recipients and their demographic and clinical correlates. Results The prevalence of depressive disorders among renal transplant recipients was (32.2%). Major depression (16.5%), adjustment disorder depressive type (9.13%) while dysthymic disorder occurred in (6.5%). Suicidality risk was present among 31.3% of the sample. Hopelessness was the commonest depressive symptoms within the depressed patients. There was a statistically significant association of depression and risk of suicidality, with age, educational attainment, employment, and the presence of side effects of medication. However, there was no significant correlation between depression or suicidality, with marital status, type of donor, duration of dialysis, and associated other medical illnesses. Despite there was no relation between gender and severity of depression, yet male recipients showed more pronounced suicidal risk. Conclusions The prevalence of depression and suicidality is quite high among post renal transplantation recipients (PRTRs). Early psychiatric evaluation and intervention together with regular long term follow-up from the multi-disciplinary team are necessary for recipients after renal transplant operation.